General, organic, and biological chemistry - Smith, Janice Gorzynski (McGraw-Hill Companies, 2013)
By relating fundamental concepts of general, organic, and biological chemistry to the everyday world, this title engages students with bulleted lists, illustrations, and step-by-step problem solving. It includes applications to biological, medical, consumer, and environmental topics